Deciding for Others Reduces Loss Aversion - Andersson, Ola; Holm, Håkan J.; Tyran, Jean-Robert; Wengström, Erik (Management science, 2016)
We study risk taking on behalf of others, both when choices involve losses and when they do not. A large-scale incentivized experiment with subjects randomly drawn from the Danish population is conducted. We find that deciding for others reduces loss aversion. When choosing between risky prospects for which losses are ruled out by design, subjects make the same choices for themselves as for others. In contrast, when losses are possible, we find that the two types of choices differ. In particular, we find that subjects who make choices for themselves take less risk than those who decide for others when losses loom. This finding is consistent with an interpretation of loss aversion as a bias in decision making driven by emotions and that these emotions are reduced when making decisions for others. This paper was accepted by Uri Gneezy, behavioral economics .